The future for health promotion - Palfrey, Colin, 1939- (Policy Press scholarship online., 2018)
Taking in to account the practical and ethical issues involved in deciding the appropriate approach to take in efforts to reduce health inequalities, the book assesses what might be the best path forward for health promotion.